Contemporary Study of Pavlovian Conditioning - Rescorla, Robert A. (The Spanish Journal of Psychology, 2003)
Pavlov’s first report on conditioning emphasized its role in allowing the animal to adjust to its environment. Contemporary theories have seen this adjustment in terms of developing accurate knowledge of the environment. Three aspects of that thinking are explored: how the animal acquires initial knowledge, how it changes its knowledge when conditions of the world change, and how it makes use of multiple knowledge representations.